2023
DOI: 10.1039/d3ja00084b
|View full text |Cite
|
Sign up to set email alerts
|

Performance of second generation ICP-TOFMS for (multi-)isotope ratio analysis: a case study on B, Sr and Pb and their isotope fractionation behavior during the measurements

Anika Retzmann,
Sebastian Faßbender,
Martin Rosner
et al.

Abstract: The second generation ICP-TOFMS is subject to IIF that does not follow the known mass dependent fractionation laws and is possibly caused by non-mass dependent fractionation and/or multiple fractionation processes with varying contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(273 reference statements)
0
2
0
Order By: Relevance
“…In previous research, ICP-TOFMS has been characterized for isotope ratio analysis in terms of mass bias and isotope fractionation for light, mid-mass, and heavy isotopes: B, Sr, and Pb. 21 This study found that precision for 208 Pb/ 206 Pb was around 0.1% when a 1000 ng mL −1 solution of Pb was analyzed. 21 In other work, RSD values from 0.41–0.06% were obtained for analysis of 208 Pb/ 206 Pb ratios from Pb standards with concentrations from 1 to 100 ng mL −1 .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In previous research, ICP-TOFMS has been characterized for isotope ratio analysis in terms of mass bias and isotope fractionation for light, mid-mass, and heavy isotopes: B, Sr, and Pb. 21 This study found that precision for 208 Pb/ 206 Pb was around 0.1% when a 1000 ng mL −1 solution of Pb was analyzed. 21 In other work, RSD values from 0.41–0.06% were obtained for analysis of 208 Pb/ 206 Pb ratios from Pb standards with concentrations from 1 to 100 ng mL −1 .…”
Section: Introductionmentioning
confidence: 86%
“…21 This study found that precision for 208 Pb/ 206 Pb was around 0.1% when a 1000 ng mL −1 solution of Pb was analyzed. 21 In other work, RSD values from 0.41–0.06% were obtained for analysis of 208 Pb/ 206 Pb ratios from Pb standards with concentrations from 1 to 100 ng mL −1 . 22 Both previously mentioned studies used 10 s acquisition times.…”
Section: Introductionmentioning
confidence: 86%